General Analysis of System Efficiency in Application of Combined Power Plants for Gas-Distribution Station - A. D. Kachan; V. M. Kopko; S. A. Kachan; M. V. Kopko; V. I. Kravtsov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes utilization of discharged heat of gas-piston engine (GPE) or contact steam-gas plants (SGP) with the purpose to heat up gas at gas-distribution stations (GDS) of combined power plants with turbine and gas-expansion units. Calculations prove significant economic efficiency of the proposed variant in comparison with the application of ordinary gas- turbine units. Technical and economic calculation is used to determine gas-piston engine or contact steam-gas plant power for specific operational conditions of gas-distribution stations and utilization rate of discharged heat.